Feng's first-integral method to traveling wave solutions of the Ostrovsky system - Kehua Li (Electronic Journal of Differential Equations, 2019)
In this paper, we apply Feng's first-integral method to study traveling wave solutions to a two-component generalization of the Ostrovsky system. We convert the two-component generalization of the Ostrovsky system to an equivalent autonomous system. Then we use the Divisor Theorem of two variables in the complex domain to seek the polynomial first-integral to this autonomous system. Through analyzing the derived first-integral, we obtain traveling wave solutions to the two-component generalization of the Ostrovsky system under certain parametric conditions.